Experimental Models to Study Podocyte Biology: Stock-Taking the Toolbox of Glomerular Research - Hagmann, Henning; Brinkkoetter, Paul T. (Frontiers in Pediatrics, 2018)
Diseases affecting the glomeruli of the kidney, the renal filtration units, are a leading cause of chronic kidney disease and end-stage renal failure. Despite recent advances in the under-standing of glomerular biology, treatment of these disorders has remained extraordinarily chal-lenging in many cases. The use of experimental models has proven invaluable to study renal, and in particular, glomerular biology and disease. Over the past 15 years, studies identified different and very distinct pathogenic mechanisms that result in damage, loss of glomerular visceral epithelial cells (podocytes) and progressive renal disease. However, animal studies and, in particular, mouse studies are often protracted and cumbersome due to the long repro-ductive cycle and high keeping costs. Transgenic and heterologous expression models have been speeded-up by novel gene editing techniques, yet they still take months. In addition, giv-en the complex cellular biology of the filtration barrier, certain questions may not be directly addressed using mouse models due to the limited accessibility of podocytes for analysis and imaging. In this review, we will describe alternative models to study podocyte biology experi-mentally. We specifically discuss current podocyte cell culture models, their role in experi-mental strategies to analyze pathophysiologic mechanisms as well as limitations with regard to transferability of results. We introduce current models in Caenorhabditis elegans, Drosophi-la melanogaster, and Danio rerio that allow for analysis of protein interactions, and principle signaling pathways in functional biological structures, and enable high-throughput transgenic expression or compound screens in multicellular organisms.